2018
DOI: 10.1111/agec.12426
|View full text |Cite
|
Sign up to set email alerts
|

The role of intellectual property rights in seed technology transfer through trade: evidence from U.S. field crop seed exports

Abstract: A panel of 134 countries over the period 1985-2010 is used to evaluate the effect of intellectual property rights (IPRs) on field crop seed imports from the United States. Based on estimating a gravity equation using the Heckman selection and Poisson fixed-effects panel econometric methods, the results indicate that membership of countries in both the International Union for the Protection of New Varieties of Plants and the Trade-Related Aspects of Intellectual Property Rights Agreement of the World Trade Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…This is consistent with other evidence showing a link between weak IP and low reinvestment rates on an individual firm and country level due to a disincentive to invest in innovation (Carlin and Mayer 2003;Fan et al 2013). The explanation for this is that weak IP in the seed industries deters exporters from entering foreign markets (Zhou et al 2018). China's seed sector has relatively small investments compared to private seed firms in many OECD countries and developing countries (Hu et al 2009).…”
Section: Effects Of Seed Ip and International Agreementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other evidence showing a link between weak IP and low reinvestment rates on an individual firm and country level due to a disincentive to invest in innovation (Carlin and Mayer 2003;Fan et al 2013). The explanation for this is that weak IP in the seed industries deters exporters from entering foreign markets (Zhou et al 2018). China's seed sector has relatively small investments compared to private seed firms in many OECD countries and developing countries (Hu et al 2009).…”
Section: Effects Of Seed Ip and International Agreementsmentioning
confidence: 99%
“…And there is evidence that stronger IP can foster international seed exchange, since some claim that plant breeder's rights are essential for developing countries to gain access to high-yielding hybrid varieties (Galushko 2012). A study by Zhou et al (2018) found that UPOV and TRIPS have had significantly positive impacts on seed exports, and therefore, increased access to improved germplasm.…”
Section: Effects Of Seed Ip and International Agreementsmentioning
confidence: 99%
“…53 Specifically, this methodology utilizes the information contained in the zero trade flows, as well as controlling for heteroskedasticity. Zhou, Sheldon, and Eum (2018) used the PPML methodology to evaluate the effect of intellectual property rights (IPRs) on US seed exports for a panel of 134 countries over the period 1985-2010. The empirical results indicate that IPR protections, such as those offered through the International Union for the 49 In current work with Kari Heerman that draws on Heerman (2020), we show that if systematic heterogeneity of agricultural productivity across countries and products is also accounted for in the gravity equation, the elasticity of trade varies significantly across countries (Heerman and Sheldon 2018).…”
Section: The Gravity Equationmentioning
confidence: 99%
“…On the other hand, strengthening IPRs protection in importing countries had a positive effect on the probability of finding new trade partners for the samples that included developing countries. Overall, the authors found that strengthening IPRs has a negative effect on agricultural trade since the signing of the TRIPS agreement, mainly in developing countries Zhou and Sheldon [26] analysed the relevance of trade of agricultural seeds and its sensitivity to the levels of intellectual property rights of a country. The authors further investigated the role of IPRs in terms of seed transfer through trade, asking the questions of whether IPRs promote access to seeds or not.…”
Section: Review Of Empirical Studies On the Relationship Between Iprsmentioning
confidence: 99%